DABCO-Catalyzed [3+2] Cycloaddition of Isatin-Derived Nitrones and Electron-Deficient Dienes via a 1,6-Addition Reaction - Luo, Zihao; Wang, Zhen; Yao, Weijun (Synthesis, 2022)
Regio-, chemo-, and diastereoselective [3+2] dipolar cycloadditions of isatin-derived nitrone ylides with penta-2,4-dienenitriles have been developed. The reaction proceeds through the organic base DABCO catalyzed 1,6-addition to linear penta-2,4-dienenitriles, followed by the intramolecular cyclization. This procedure is capable of tolerating a relatively wide range of nitrone ylides under mild conditions, facilitating the preparation of various 1′-hydroxyspiro[indoline-3,2′-pyrrolidine] derivatives.
Keywords: [3+2] cycloaddition; 1,6-addition; regioselectivity; nitrone ylide; spirooxindole; diastereoselectivity